Trabajar la Educación Ambiental en la Educación Infantil, utilizando los principios del enfoque CTSA - Dutra Filho, João Moreira; Maciel, Maria Delourdes (Revista Latino-americana de Ambiente Construído & Sustentabilidade, 2023)
Early Childhood Education is an important stage of Basic Education and fundamental for the formation of our children, therefore, in this work, the proposal was to work on Environmental Education with children, from non-formal spaces, more specifically the Barreiros Municipal Park ( BMP), guided by the principles of Education Science, Technology, Society and Environment (STSE). This work is part of a doctoral thesis. This is a qualitative intervention-action-pedagogical research. Discursive Textual Analysis was used for data analysis. During the development of the work, a didactic sequence was carried out that provided for an initial discussion on the subject, a visit to the site (BMP) and carrying out different activities on the visit made. The results showed the development of critical thinking, argumentation, environmental perception and concern with issues related to nature conservation.